Besides from what you see: analysis of social representation assigned to the medical professional through web sites available on the Internet. - Lucas Alexandre Gonçalves do Nascimento GOMES; Felipe Santana RODRIGUES; Gustavo Bacelar Fontenele ARAÚJO; Marny Ryann Rapôso FERREIRA; Vanessa Gonçalves COSTA; Fábio Solon TAJRA; José Ivo dos Santos PEDROSA (Universidade de Brasília, 2015)
Images can convey strong associations with symbols. This type of interpretation applies to distinct areas, including Health. In the images which portray the medical professional, this is not different. However, there has been much questioned what symbol is related to this profession association. Currently, with the increased range of Internet search websites and its high number of access, a few images and symbols which connote or denote medical sites can be seized from a simple search. In this perspective, this study aims to analyze the social representation assigned to the medical professional through search websites as well as the symbols that are associated with this profession. This is an exploratory-descriptive study of qualitative and quantitative approach in which images were researcherd in five search sites available on different web, namely: www.google.com, www.ask.com, www.bing.com, www.yahoo.com and www.uol.com. For this, descriptors such as "médico", "médica" and "profissionalmédico" were used. All posted images were collected in a period of 30 continuous days. Then, images were grouped into categories. It is worth mentioning, the images that only portray the everyday and images that portray show cartoons and famous or historical personalities were excluded. The images in different internet search websites were classified into diverse categories, among them lovingness, religion, leadership, teamwork, distance between doctor and patient, the profession, controversial, personal protective equipment, stethoscope, symbol, hospital equipment, records health and others. The categories that presented more frequently were: the profession, teamwork, stethoscope and health record. From this, we might infer that the doctor is a figure often linked to work, mainly because it routinely represented by instruments of his profession. When not represented by these instruments, the doctor is very portrayed and remembered by the exercise of their profession. Although there is controversy about the figure of the medical professional, is customarily stigmatization and constant media appeal to pass the idea of a professional distance, the doctor is seen as someone who often comforting or is in close contact with your patient.